Towards Situated Collaboration - Bohus, Dan; Kamar, Ece; Horvitz, Eric (In NAACL Workshop on Future Directions and Challenges in Spoken Dialog Systems: Tools and Data, 2012)
We outline a set of key challenges for dialog management in physically situated interactive systems, and propose a core shift in perspective that places spoken dialog in the context of the larger collaborative challenge of managing parallel, coordinated actions in the open world.